2021
DOI: 10.1155/2021/6619170
|View full text |Cite
|
Sign up to set email alerts
|

The Therapeutic Potential of Inflamed Gingiva-Derived Mesenchymal Stem Cells in Preclinical Studies: A Scoping Review of a Unique Biomedical Waste

Abstract: Searching for considerable abundance, simple, and accessible sources in stem cell-based therapy opens the door for isolation of a new population of oral/dental stem cells known as inflamed gingiva-derived mesenchymal stem cells, which have recently come to light with promising therapeutic potential in tissue regenerative therapy. Following the Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for Scoping Reviews guidelines, this scoping review is aimed at highlighting the possible th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Santoso et al also found that MSCs transplantation can improve cardiac function after myocardial infarction by regulating autophagy of hypoxia-damaged myocardial cells [ 63 ]. However, at the same time, studies have shown that stem cells have a low survival rate in the inflammatory, ischemic and hypoxic environment, and only 1% of stem cells can survive more than 4 days after transplantation [ 64 , 65 ]. The low number of stem cells may not be enough to play a therapeutic role.…”
Section: Discussionmentioning
confidence: 99%
“…Santoso et al also found that MSCs transplantation can improve cardiac function after myocardial infarction by regulating autophagy of hypoxia-damaged myocardial cells [ 63 ]. However, at the same time, studies have shown that stem cells have a low survival rate in the inflammatory, ischemic and hypoxic environment, and only 1% of stem cells can survive more than 4 days after transplantation [ 64 , 65 ]. The low number of stem cells may not be enough to play a therapeutic role.…”
Section: Discussionmentioning
confidence: 99%
“…9 Neural-crest-derived GMSCs (N-GMSCs) and mesoderm-derived GMSCs (M-GMSCs) are two subpopulations of gingival mesenchymal stem/progenitor cells, with N-GMSCs having a stronger ability to develop into neural cells than M-GMSCs. 10 Alternatively, a loose ectomesenchyme-derived connective tissue called dental follicle surrounds the enamel organ and dental papilla of the growing tooth germ. The DFSCs are comprised of a series of pluripotent stem cells formed from neural crest cells originating from the ectoderm.…”
Section: Origin and Distinct Phenotypes Of Stem Cells Within The Peri...mentioning
confidence: 99%
“…9 Neural-crest-derived GMSCs (N-GMSCs) and mesoderm-derived GMSCs (M-GMSCs) are two subpopulations of gingival mesenchymal stem/progenitor cells, with N-GMSCs having a stronger ability to develop into neural cells than M-GMSCs. 10…”
Section: Origin and Distinct Phenotypes Of Stem Cells Within The Peri...mentioning
confidence: 99%
“…Surprisingly, they can maintain telomerase activity in a prolonged culture with no tumorigenesis. According to the literature, GMSCs have high potential in the regeneration of alveolar bone defects, periodontium, oral neoplasms, and peri-implantitis [37][38][39]. To date, several studies have been published concerning the use of GMSCs in dental tissue regeneration.…”
Section: Osteogenic Potential Of Dental Tissue-derived Mscsmentioning
confidence: 99%